Tomographic Imaging of Traveling Ionospheric Disturbances Using GNSS and Geostationary Satellite Observations. Issue 3 (2nd March 2020) - Bolmgren, Karl; Mitchell, Cathryn; Bruno, Jon; Bust, Gary
Abstract: Traveling ionospheric disturbances (TIDs) are the manifestations of atmospheric gravity waves in the ionosphere. These disturbances have practical importance because they affect satellite navigation technologies such as Global Navigational Satellite System (GNSS), causing degradation in precise positioning applications. They also have scientific significance as their generation mechanisms and propagation are not fully understood. While there are specific instruments that can measure TIDs in certain locations, there is a need for wide‐area observations across extended geographical regions to continuously monitor their onset and spatial and temporal characteristics. This paper evaluates the use of observations from ground‐based geodetic GNSS receivers to image TIDs using ionospheric tomography and data assimilation. Certain GNSS receivers also monitor signals from geostationary (GEO) satellites, which provide a unique perspective on the TID. The advantage of using the GEO data is investigated. A computerized simulation of GNSS observations is used for evaluation of the Multi‐Instrument Data Analysis System (MIDAS) with GEO and regular GNSS geometry. The simulated observations are generated by integrating the electron density through a modeled TID‐perturbed dynamic ionosphere between actual receiver and satellite positions. The output 3‐D electron density image series generated from the synthetic data by the MIDAS ionospheric tomography and data assimilation algorithm are compared with the input model ionosphere. Results show that GEO geometry improves the reconstruction of medium‐scale TIDs (MSTIDs) and smaller LSTIDs in cases where the movement of regular GNSS satellites in Medium Earth orbit (MEO) may otherwise introduce distortions to the observations. Key Points: Ionospheric tomography with GEO geometry is tested by simulation Using GEO geometry improves tomographic imaging of MSTIDs Regular GNSS‐MEO geometry or a combination of GEO and GNSS‐MEO geometry is preferred for LSTIDs